2015
DOI: 10.1017/ice.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Needle-Stick Injuries in Healthcare Facilities: A Meta-Analysis

Abstract: OBJECTIVE To estimate the summary effectiveness of different needle-stick injury (NSI)-prevention interventions. DESIGN We conducted a meta-analysis of English-language articles evaluating methods for reducing needle stick, sharp, or percutaneous injuries published from 2002 to 2012 identified using PubMed and Medline EBSCO databases. Data were extracted using a standardized instrument. Random effects models were used to estimate the summary effectiveness of 3 interventions: training alone, safety-engineered d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 36 publications
2
52
0
2
Order By: Relevance
“…14 According to a recent meta-analysis, training, safety-engineered devices, and training combined with safety-engineered devices reduced the rate of needlestick injuries by 34%, 49%, and 62%, respectively. 15 Our study identified that a considerable proportion of percutaneous injuries are now associated with safety-engineered devices. Further, the frequency of percutaneous injuries associated with safety-engineered devices is now similar to the level of overall exposures to mucous membrane/ non-intact skin, suggesting the necessity for improving measures to prevent exposures from the use of HCP-activated safety-engineered devices as well as conventional devices.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…14 According to a recent meta-analysis, training, safety-engineered devices, and training combined with safety-engineered devices reduced the rate of needlestick injuries by 34%, 49%, and 62%, respectively. 15 Our study identified that a considerable proportion of percutaneous injuries are now associated with safety-engineered devices. Further, the frequency of percutaneous injuries associated with safety-engineered devices is now similar to the level of overall exposures to mucous membrane/ non-intact skin, suggesting the necessity for improving measures to prevent exposures from the use of HCP-activated safety-engineered devices as well as conventional devices.…”
Section: Resultsmentioning
confidence: 91%
“…We demonstrated significant overall reduction in BBFE and percutaneous injuries that may be in part due to the impact of safety-engineered devices and supported previous studies showing successful reduction of overall percutaneous injuries. 11,14,15 Notably, safety-engineered devices worked well to decrease the incidence of percutaneous injuries from the 6 37 2 11 0 2 1 0 1 0 0 4 Total 745 1716 227 367 38 125 122 16 66 51 47 629 2001 Act to 2006, but this positive impact of safety-engineered devices stabilized after 2006. Therefore, we need new interventions aimed at further reducing the injuries among HCP in addition to using safety-engineered devices.…”
Section: Resultsmentioning
confidence: 99%
“…Other examples of novel approaches to replace typical injection procedures include microneedles, mouth strips, nanopatches, mucosal administration, and edibles (Ravi, Sadhna, Nagpaal, & Chawla, ; Saroja, Lakshmi, & Bhaskaran, ). Such needle‐free methods could also potentially reduce needle‐stick injuries which pose safety concerns in healthcare settings (Tarigan, Cifuentes, Quinn, & Kriebel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although being in effect for several years, The Directive 2010/32/EU “Prevention from sharp injuries in the hospital and healthcare sector” ( 12 ) has not been implemented in Croatian laboratories. There is an ample of evidence that safe-sharp laboratory materials significantly lower risk of needle-stick injuries ( 13 ). Even though the main reason for delaying implementation of safe-sharp equipment is increased cost for the laboratory, the overall cost for the diagnostics and treatment of needle-stick injuries for the healthcare in general is higher ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%